Actomyosin-assisted pulling of lipid nanotubes from lipid vesicles and cells - Jahnke, Kevin; Maurer, Stefan J.; Weber, Cornelia; Hernandez Bücher, Jochen Estebano; Schönit, Andreas; D'Este, Elisa; Cavalcanti-Adam, Elisabetta A.; Göpfrich, Kerstin (Nano letters, 2022)
Molecular motors are pivotal for intracellular transport as well as cell motility and have great potential to be put to use outside cells. Here, we exploit engineered motor proteins in combination with self-assembly of actin ﬁlaments to actively pull lipid nanotubes from giant unilamellar vesicles (GUVs). In particular, actin ﬁlaments are bound to the outer GUV membrane and the GUVs are seeded on a heavy meromyosin-coated substrate. Upon addition of ATP, hollow lipid nanotubes with a length of tens of micrometer are pulled from single GUVs due to the motor activity. We employ the same mechanism to pull lipid nanotubes from diﬀerent types of cells. We ﬁnd that the length and number of nanotubes critically depends on the cell type, whereby suspension cells form bigger networks than adherent cells. This suggests that molecular machines can be used to exert forces on living cells to probe membrane-to-cortex attachment.